2009
DOI: 10.1007/s00535-009-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed surface coil for endoluminal MRI, depiction of pig gastric wall layers and vascular architecture in ex vivo study

Abstract: High-spatial-resolution MR imaging using a surface coil placed closely to the gastric wall enabled the differentiation of porcine gastric wall layers and the depiction of the blood vessels in proper muscle layer in this experimental study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Endoluminal MR imaging was able to show 3-6 layers of the resected porcine stomach [16,17,20,22,24]. In our study, the living porcine gastric wall structure was depicted as four layers.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Endoluminal MR imaging was able to show 3-6 layers of the resected porcine stomach [16,17,20,22,24]. In our study, the living porcine gastric wall structure was depicted as four layers.…”
Section: Discussionmentioning
confidence: 97%
“…Also, several studies have already reported on the diagnostic performance of endoluminal MR imaging [15][16][17][18][19][20][21][22][23][24][25]. Yamada et al [20] reported that the assessments of the depth of mural invasion obtained with high spatial resolution MR imaging accurately correlated with the results of histopathologic staging in 93% of their resected gastric carcinoma cases.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations